Utilization of Eggshell Powder as a Green Mortar Material - Kechkar CHIRAZ; Benamara FATIMA ZOHRA; Nigri GHANIA; Hebhoub HOURIA; Alsayadi HAMID; Messaoudi KARIMA (Medžiagotyra)
Recycling waste in cementitious materials promotes sustainable construction. It helps to prevent the depletion of natural resources while also reusing abundant recyclable wastes. Eggshells are one of these wastes that is being generated in large quantities because eggs are not expensive and have high nutritional value. On the other side, eggshell has a high content of calcium carbonate. It has a similar composition to the limestone powder used to produce Portland cement. This work investigates the effect of replacing a part of the cement with eggshell powder on mortar properties. The substitution rates were 5 %, 10 %, and 15 % of the cement’s mass. The results were compared with those of an ordinary mortar for the following properties: workability, compressive strength, flexural tensile strength, density in the hardened state, water absorption by total immersion, porosity accessible to water, depth of water penetration under pressure and chemical attack by sulfuric acid. The experimental results show that adding eggshell powder as a partial cement substitute up to 10% improved workability, increased compressive strength by about 10 % and flexural tensile strength by about 20 %, reduced density, and produced a more durable mortar by reducing porosity, water absorption, and water penetration depth under pressure. On the other hand, it decreased resistance to chemical attack by sulfuric acid. Thus, eggshell powder could be used in future construction materials to reduce carbon dioxide emissions.